Anyway ou le mode énonciatif du savoir en prendre et en laisser - Catherine Filippi-Deswelle (Anglophonia)
This study aims to show that the adverb ANYWAY has a variety of syntactic positions, initial, medial or final, as well as a wide range of semantic and argumentative values in discourse, namely concessive, additive, rectifying, resumptive, elliptical or concluding, which can be brought down to one underlying operation : a distancing operation. Carried out within the framework of the Theory of Enunciative Operations, this paper accounts for the syntactic behaviour and the differing values in context of ANYWAY in terms of otherness and change of orientation in the notional domain. The speaker ceases to endorse a previous utterance (or part of it) with a view to endorse a more appropriate one and convince the hearer to do the same.